The Effect of Regions on Agricultural Enterprises in Szigetköz Hungary: The effect of agglomeration on settlements’ agriculture - Horváth, Eszter (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2017)
The analysis demonstrated in this study is the first part of a wide range of investigations. This study includes the history of the farming practice in the region and deals with registered agricultural joint ventures in the region. In my research work I tried to answer the question: How can regional characteristics differentiate farming practice and the number of agricultural enterprises and the profile of their activities. There is a major difference to be detected in the numbers and activities of agricultural enterprises within a certain region. Approaching to Győr, the region’s main city and seat of the county, we can observe a decrease in the numbers of agricultural enterprises although the arable land there is excellent. At the same time the number of inhabitants in those rural communities increases together with the proportion of houses in areas that were earlier used for farming and as a result there is a higher rate of population with solvent demands as well. Agricultural services gain on importance in the communities in the agglomeration of Győr constantly.